A Study on Quality Control of NFT Hydrophonic Pakcoy (Brassica rapa chinensis) in XYZ Farm, Bogor Regency - Agustina Senjayani; Naufal Fahrur Rajhi; Eny Dwiningsih (PUCUK : Jurnal Ilmu Tanaman, 2024)
Besides being known for its efficiency, simplicity, and productivity, the NFT Hydroponic technique is popularly chosen for its high effectiveness in producing high-quality hydroponic vegetables with excellent plant health. This research aims to study the quality control of Hydroponic Pakcoy produced using the NFT Technique at XYZ Hydroponic Farm, Bogor Regency, through (1) identification of types and levels of damage, (2) analysis of factors causing damage; (3) proposing alternative improvements that can be made. Analysis was conducted using statistical quality control (SQC). The results showed the level of damage to hydroponic Pakcoy at XYZ hydroponic farm, which showed uncontrolled damage consisting of damaged leaves, damaged stems, and abnormal shapes or sizes. Fishbone analysis reveals the causes of damage, including lack of knowledge and negligence of labor, how to harvest, and greenhouse damage. Based on the causes of damage, recommendations for improvement that can be made are to create criteria and goals for prospective internship workers, increase the intensity of supervision, reconstruct the greenhouse, and create a slide desk.